Efficacy of Prophylactic Cerclage in Women with a Single History of Mid-Trimester Pregnancy Loss with Painless Cervical Dilation: A Retrospective Cohort Study - Atsuko Tezuka; Hiroyuki Tsuda; Yumiko Ito; Tomoko Ando (Clinical and Experimental Obstetrics & Gynecology)
Background: Recently, serial ultrasound assessment of cervical length has been proposed as an alternative management of history-indicated cerclage. To investigate the efficacy of prophylactic cerclage among women who had previously experienced mid-trimester pregnancy loss by comparing the outcomes between women who chose history-indicated cerclage and those who chose serial ultrasound assessment. Methods: We examined the medical records of women who delivered at our hospital between 2010 and 2018 and extracted cases with a history of mid-trimester pregnancy loss between 14 and 25 weeks' gestation. We compared the women with and without history-indicated cerclage. For women who choose expectant management, cervical length was assessed by transvaginal ultrasound every two weeks, and ultrasound-indicated cerclage was performed. The primary outcome was preterm birth before 28 or 34 weeks. Results: The study criteria were met by 63 women; among these, 28 had received history-indicated cerclage. The incidence of preterm birth at 28 and 34 weeks was similar between the two groups. However, among the 30 women who experienced painless cervical dilation at prior pregnancy loss, history-indicated cerclage showed significant low preterm birth rate compared with expectant management: 2/22 (9.1%) vs. 4/8 (50.0%) at <28 weeks (p = 0.029) and showed a lower preterm birth rate: 3/22 (13.6%) vs. 4/8 (50.0%) at <34 weeks (p = 0.06). Conclusions: History-indicated cerclage can be considered in women with a history of mid-trimester pregnancy loss who experience painless cervical dilation.